2019
DOI: 10.3390/en12101867
|View full text |Cite
|
Sign up to set email alerts
|

Response-Based Assessment of Operational Limits for Mating Blades on Monopile-Type Offshore Wind Turbines

Abstract: Installation of wind-turbine blades on monopile-type offshore wind turbines is a demanding task. Typically, a jack-up crane vessel is used, and blades are individually lifted from the vessel deck and docked with the preinstalled hub. During the process of mating, large relative motions are developed between the hub and root due to combined effects of wind-generated blade-root responses and wave-generated monopile vibrations. This can cause impact loads at the blade root and induce severe damages at the blade-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Common response surfaces (RS) are polynomials, Kriging models, and ANNs. Applications of RS in offshore engineering can be found in [15][16][17]. In this work, we considered backpropagation neural networks to represent the RS, and used the combined damage index [ , ∆Ψ] and the element damages (ΔE) as the training data for the networks.…”
Section: B Damage Identification Methodsmentioning
confidence: 99%
“…Common response surfaces (RS) are polynomials, Kriging models, and ANNs. Applications of RS in offshore engineering can be found in [15][16][17]. In this work, we considered backpropagation neural networks to represent the RS, and used the combined damage index [ , ∆Ψ] and the element damages (ΔE) as the training data for the networks.…”
Section: B Damage Identification Methodsmentioning
confidence: 99%
“…Several numerical studies have been carried out investigating turbine behavior during turbine installation. Most studies concluded that wind-induced motions of the blade and wind and wave-induced motions of the tower limit the installation of blades [28][29][30][31].…”
Section: Field and Simulation Datamentioning
confidence: 99%
“…Majority of the misalignment occurs till 30°, with frequency being less than 5% for wind-wave misalignment greater than 60° ( Bachynski et al 2014). Currently, there are limited published literature sources (Jiang et al 2018;Verma et al 2019c;Verma et al 2019d;Verma et al 2020a;Verma et al 2020b) dealing with the effects of wind-wave misalignment on the installation phases of OWTs, although several studies in the past emphasised operational and parked conditions of OWTs for design purposes. Barj et al (2014), Bachynski et al (2014) and Zhou et al (2017) investigated the effect of misalignment on the operational loads for floating OWTs, whereas Fischer et al (2011) investigated the effect of misalignment on monopile-type OWTs.…”
Section: Article Highlightsmentioning
confidence: 99%